Quality of Tie Dye Using Papaya Leaves Extract (Carica papaya L.) - Nahdiyah, Ayu; Kusumastuti, Adhi (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2024)
The Papaya plant is one type of plant that is widely cultivated in Indonesia. Papaya leaves contain chlorophyll, tannins, flavonoids, alkaloids, steroids, saponins, and triterpenoids which can be used as basic ingredients for the manufacture of natural dyes for textiles. Utilization of papaya leaves as natural dyes can reduce the impact of environmental damage caused by synthetic dyes. This study aims to determine the quality of color strength, color fastness to detergent washing, and motive sharpness on primissima mori fabric using tie-dyeing technique with variations in the pH of papaya leaf extract and the mordant used is mordant alum, quicklime, and tunjung. This research is a type of experimental research. The data collection technique used was a laboratory test. The data analysis technique used is descriptive analysis. The results of the descriptive analysis showed that the darkest color strength test results were produced by mordant tunjung pH 6 with a reflectance value of 3.51% and a transmittance value of 96.49% including very dark criteria. The best test values ​​for color fastness to detergent washing were alum mordant at pH 2 and pH 12 and quicklime mordant at pH 2 with an average gray scale value of 4-5 in the good category. The test value for the sharpest tie dye motive is the mordant tunjung pH 6 with a reflectance value of 3.51% and a transmittance value of 103% including very sharp criteria. The conclusion from several test results shows that the use of different pH variations and types of mordant can affect the results of the quality of dyeing on fabrics.